Pain Control After Shoulder Arthroscopy: A Systematic Review of Randomized Controlled Trials With a Network Meta-analysis. Issue 8 (July 2021) - Hurley, Eoghan T.; Maye, Andrew B.; Thompson, Kamali; Anil, Utkarsh; Resad, Sehar; Virk, Mandeep; Strauss, Eric J.; Alaia, Michael J.; Campbell, Kirk A.
Background: Shoulder arthroscopy is one of the most commonly performed orthopaedic procedures used to treat a variety of conditions, with >500, 000 procedures performed each year. Purpose: To systematically review the randomized controlled trials (RCTs) on pain control after shoulder arthroscopy in the acute postoperative setting and to ascertain the best available evidence in managing pain after shoulder arthroscopy to optimize patient outcomes. Study Design: Systematic review and meta-analysis. Methods: A systematic review of the literature was performed based on the PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) guidelines. Studies were included if they were RCTs evaluating interventions to reduce postoperative pain after shoulder arthroscopy: nerve blocks, nerve block adjuncts, subacromial injections, patient-controlled analgesia, oral medications, or other modalities. Meta-analyses and network meta-analyses were performed where appropriate. Results: Our study included 83 RCTs. Across 40 studies, peripheral nerve blocks were found to significantly reduce postoperative pain and opioid use, but there was no significant difference among the variable nerve blocks in the network meta-analysis. However, continuous interscalene block did have the highest P-score at most time points. Nerve block adjuncts were consistently shown across 18 studies to prolong the nerve block time and reduce pain. Preoperative administration was shown to significantly reduce postoperative pain scores ( P < .05). No benefit was found in any of the studies evaluating subacromial infusions. Conclusion: Continuous interscalene block resulted in the lowest pain levels at most time points, although this was not significantly different when compared with the other nerve blocks. Additionally, nerve block adjuncts may prolong the postoperative block time and improve pain control. There is promising evidence for some oral medications and newer modalities to control pain and reduce opioid use. However, we found no evidence to support the use of subacromial infusions or patient-controlled analgesia.